2018
DOI: 10.1016/j.idcr.2018.e00474
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary mucormycosis in an adolescent female with type 1 diabetes mellitus

Abstract: HighlightsDiabetes is present in 15% of pediatric patients with mucormycosis [1–2].Treatment includes amphotericin B, as well as surgical debridement for invasive disease.High index of suspicion is required as delay of treatment leads to disseminated disease.The mortality rate is near 50%, while for disseminated disease is almost 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is a less common opportunistic fungal infection compared to Candida and Aspergillus species [1]. There are six most commonly reported forms which include rhinocerebral, pulmonary, cutaneous, gastrointestinal, disseminated, and uncommon presentations [2,3]. The relative incidence of pulmonary mucormycosis (PM) to other clinical form incidence in literature is about 25% [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is a less common opportunistic fungal infection compared to Candida and Aspergillus species [1]. There are six most commonly reported forms which include rhinocerebral, pulmonary, cutaneous, gastrointestinal, disseminated, and uncommon presentations [2,3]. The relative incidence of pulmonary mucormycosis (PM) to other clinical form incidence in literature is about 25% [4].…”
Section: Introductionmentioning
confidence: 99%
“…No underlying immunodeficiency was identified, so the reason for his sensitivity to this opportunistic infection is unclear. Pulmonary mucormycosis has been described in patients in diabetic ketoacidosis [4], and it is speculated that a combination of hyperglycemia and ketoacidosis suppresses innate immune function and promotes fungal spread [4]. However, there is no analogous mechanism in type two diabetes [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and management of pulmonary mucormycosis in children is poorly described. One review article described 44 definitive cases identified by registry, of which 63% were associated with malignancy or bone marrow transplant, and 48% of all patients were treated with a combination of antifungal medication and surgery [4]. Combination therapy was associated with lower mortality; however, additional details, such as underlying etiology and surgical intervention, were not reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is a less common opportunistic fungal infection compared to Candida and Aspergillus species [1]. There are six most commonly reported forms which include rhinocerebral, pulmonary, gastrointestinal, cutaneous, disseminated, and uncommon presentations [2,3]. The relative incidence of pulmonary mucormycosis (PM) to other clinical form incidence in literature is about 25% [4].…”
Section: Introductionmentioning
confidence: 99%